2022
DOI: 10.3389/fmicb.2022.923664
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Valorization of Lignin to Bioplastic by Genome-Reduced Pseudomonas putida

Abstract: As the most abundant natural aromatic resource, lignin valorization will contribute to a feasible biobased economy. Recently, biological lignin valorization has been advocated since ligninolytic microbes possess proficient funneling pathways of lignin to valuable products. In the present study, the potential to convert an actual lignin stream into polyhydroxyalkanoates (PHAs) had been evaluated using ligninolytic genome-reduced Pseudomonas putida. The results showed that the genome-reduced P. putida can grow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous study also showed that the PHA accumulation of the engineered P. putida could be affected at higher lignin concentration. ,, …”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous study also showed that the PHA accumulation of the engineered P. putida could be affected at higher lignin concentration. ,, …”
Section: Resultsmentioning
confidence: 86%
“…Previous study also showed that the PHA accumulation of the engineered P. putida could be affected at higher lignin concentration. 6,26,28 3HD was identified as the primary component in PHA when lignin hydrolysate was used as the sole carbon source. P. putida KT2440 cultivated on the sole APL substrate also successfully synthesized PHA containing mainly 55% 3HD.…”
Section: Fermentation Strategy Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyhydroxyalkanoates (PHA) are one of potential bioproducts that can be produced from lignin or lignin derivatives via microbial fermentation 6,7 . PHA are bio‐polyesters, naturally evolved as energy storage compound by selected group of microbes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Polyhydroxyalkanoates (PHA) are one of potential bioproducts that can be produced from lignin or lignin derivatives via microbial fermentation. 6,7 PHA are bio-polyesters, naturally evolved as energy storage compound by selected group of microbes. 8 The bioplastics are viewed as environmental-friendly, a key material to replace fossilbased plastics, and can be applied among a multitude of diverse materials ranging from packaging to high performance med-tech applications.…”
mentioning
confidence: 99%